Optimal Portfolio Analysis Using Markowitz and Single Index Model - Maulana, Yasir; Meilaniy, Windy Dwi; Yusuf, Ayus Ahmad (Universitas Bina Sarana Informatika, 2025)
This study aims to determine the composition of the optimal portfolio formation results of the Markowitz Model and Single Index Model. This study also aims to compare the results of optimal portfolio formation and performance of the Markowitz Model and Single Index Model. The population in this study are all stocks included in the LQ45 index listed on the Indonesia Stock Exchange for the period 2018-2022. The research sample is stocks that are consistently listed in the LQ-45 index during the 2018-2022 period. The number of research samples based on these conditions was 27 stocks. The results of this study are: In the Markowitz Model, 5 optimal portfolio-forming stocks are obtained, namely ADRO (49%), ANTM (22%), BBCA (7%), ICBP (5%), and KLBF (16%). With a portfolio return rate of 0.025382 (2.54%) and a portfolio risk of 0.081342 (8.13%). In the Single Index Model, 9 optimal portfolio-forming stocks are obtained, namely UNTR (15.18%), PTBA (3.38%), MNCN (4.15%), ICBP (35.59%), EXCL (6.62%), BBTN (0.92%), BBCA (32.55%), ANTM (0.04%) and ADRO (1.56%). With a portfolio return rate of 0.02066 (2.1%) and a portfolio risk of 0.04005 (4%). The results of the independent sample t-test processing of the return show that there is no difference between the Markowitz Model return and the Single Index Model return.